Tinjauan Sistematis Blockchain Untuk Penguatan Keamanan Data Pada Infrastruktur Digital Indonesia: Studi Literatur terhadap Implementasi Teknologi Blockchain pada Sektor Strategis Nasional - Sitorus, Kelvin; Tan, Leonardo; Irsan Irsan; Marcelino, Albert; Christian Christian; Josten Josten (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The rapid growth of digital transformation in Indonesia has created an urgent need for reliable and sustainable data security mechanisms. This study aims to systematically review the application of blockchain technology in strengthening data security within Indonesia’s digital infrastructure. The research employed a systematic literature review of national and international articles published between (2023-2025) that met predefined inclusion criteria. Analysis of 25 selected studies revealed that blockchain significantly contributes to ensuring data integrity, confidentiality, and transparency through decentralization, encryption, and immutable transaction records. The findings indicate that blockchain adoption in Indonesia is most prevalent in the financial, healthcare, education, and supply chain sectors, although challenges remain in terms of regulation, implementation costs, and infrastructure readiness. This study highlights blockchain’s substantial potential as a strategic solution for enhancing data security and supporting the resilience of Indonesia’s digital ecosystem.